Integrating traditional knowledge in faunal conservation (Zoological Records and Reviews, 2025)
Traditional and local ecological knowledge (TLK) -- the cumulative body of knowledge, practices, and beliefs about therelationships between living beings and their environment that has evolved by adaptive processes and been handeddown through generations -- holds substantial untapped potential for faunal conservation, particularly in extendingtemporal baselines for species distribution and abundance, detecting cryptic or range-restricted species, and informingculturally appropriate conservation interventions in landscapes where human livelihoods are intertwined with biodiversity.This review synthesises evidence from 172 primary studies (2000-2025) examining the integration of TLK into Europeanand global faunal conservation programmes. We evaluate six integration modalities -- historical baseline extension,species occurrence verification, threat identification, management co-design, monitoring co-implementation, andgovernance participation -- across 42 case studies from European pastoral, coastal, and forest landscapes. TLK-basedhistorical baseline extension increases documented species observation windows by a mean 48.4 +- 18.4 years beyondscientific survey records, with highest extensions for large mammals (mean 64.4 years) and coastal fish (mean 72.4years). TLK verification of modelled species distributions corrected false absence predictions for 28.4% of cells inEuropean large mammal range maps. Community co-designed monitoring programmes show 42% higher volunteerretention than researcher-designed programmes in paired comparisons. Key barriers -- epistemic validation challenges,intellectual property concerns, power asymmetries between knowledge holders and research institutions, and absence ofTLK integration standards in EU conservation policy frameworks -- are analysed alongside practical co-productionframeworks. Guidelines for ethical and scientifically rigorous TLK integration in European faunal conservation arepresented.